1991
DOI: 10.1021/jm00113a009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of azabicyclic esters and oxadiazoles as ligands for the muscarinic receptor

Abstract: The link between the cognitive deficit associated with Alzheimer type dementia and the loss of cholinergic function in the disease provides a basis for examining muscarinic agonists as potential therapeutic agents. This paper describes the design and synthesis of novel azabicyclic methyl esters as ligands for the muscarinic receptor. Replacement of the methyl ester by a 3-methyl-1,2,4-oxadiazole ring produces potent metabolically more stable muscarinic agonists capable of penetrating the central nervous system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
114
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(115 citation statements)
references
References 0 publications
1
114
0
Order By: Relevance
“…Also, a report from the muscarinic literature suggested that 1-azabicyclo-[3.2.1]octane can function as an effective isostere of quinuclidine [9]. Chlorobenzamide (±)-1 was initially prepared in racemic form (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Also, a report from the muscarinic literature suggested that 1-azabicyclo-[3.2.1]octane can function as an effective isostere of quinuclidine [9]. Chlorobenzamide (±)-1 was initially prepared in racemic form (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and the evaluation of several derivatives of the group in question, where the affinity by muscarinic receptors is strong, puts them among the possible drugs for the treatment of Alzheimer´s disease (ORLEK et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The oxadiazole moiety is an important structure unit in drugs and chemical materials [12]. Among these oxadiazoles, [1,2,4]-oxadiazoles are gaining interest in the medicinal chemistry [13] and shows numerous biological activities including muscarinic agonists [14], dopamine transporters [15], benzodiazepine receptor partial agonists [16], nematocidal, fungicidal, and microbicides [17], immunosuppressants [18], Fab I inhibitors as antibacterial agents [19], antiplatelet and antithrombotic agents [20], etc. Also, oxadiazoles plays an important role as bioisosteres for amides and esters [21].…”
Section: Introductionmentioning
confidence: 99%